2022
DOI: 10.33712/mana.1111467
|View full text |Cite
|
Sign up to set email alerts
|

Havacılık Sektöründe İnovasyon Stratejilerinin Etkileri

Abstract: As a result of increasing aviation activities, enterprises need to create innovations in the products and services they produce in order to maintain their market share and ensure the sustainability of the enterprises. When these innovations are made strategic plans for businesses, they guide businesses to adapt to changing conditions in the aviation sector, which has a high uncertainty environment. In this sense, the projection of the strategies created in the enterprise to all departments and the adoption by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
0
0
4
Order By: Relevance
“…Bu durumda THY gibi güçlü markalar süper marka olarak rekabet üstünlüklerini kullanarak yaşamaya devam ederken, devletin deprem sonucu artan kamu yükünü azaltmak için yapıları zayıflayan hava yolu şirketlerini teşvik yoluyla destekleme konusunda daha fazla çekimser kalmak zorunda kalabilecektir (Var, & Gürdal, 2021). Bu açıdan hava yolu şirketleri markalaşmaya ve ittifaklar kurmaya zorlayan şartları değerlendirerek bu yönde bir eğilim içine girmeleri ekonomik gelecekleri açısından bir çıkış yolu olarak görülebilir (Sumerli Sarıgül & Coşkun, 2022).…”
Section: Makroekonomik Krizlerde Marka İttifakları Ve Thy öRneğiunclassified
“…Bu durumda THY gibi güçlü markalar süper marka olarak rekabet üstünlüklerini kullanarak yaşamaya devam ederken, devletin deprem sonucu artan kamu yükünü azaltmak için yapıları zayıflayan hava yolu şirketlerini teşvik yoluyla destekleme konusunda daha fazla çekimser kalmak zorunda kalabilecektir (Var, & Gürdal, 2021). Bu açıdan hava yolu şirketleri markalaşmaya ve ittifaklar kurmaya zorlayan şartları değerlendirerek bu yönde bir eğilim içine girmeleri ekonomik gelecekleri açısından bir çıkış yolu olarak görülebilir (Sumerli Sarıgül & Coşkun, 2022).…”
Section: Makroekonomik Krizlerde Marka İttifakları Ve Thy öRneğiunclassified
“…Furthermore, studies can be found in the literature that have used both the MEREC and CoCoSo methods together. MEREC and CoCoSo methods were used together in decision problems such as performance evaluation of insurance companies (Bektaş, 2022), selection of waste and recycled materials for road construction (Marinkovic et al, 2022), aircraft selection for flight schools (Özdağoğlu et al, 2022), assessment of urban transportation plans (Simic et al, 2022), financial performance evaluation of lodging and tourism industries (Ghosh & Bhattacharya, 2022), evaluation of countries' innovation performance (Ecer & Ayçin, 2023), and assessment of airport service quality (Sümerli Sarıgül et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%